PAPSS2 mutations cause autosomal recessive brachyolmia - ELÇİOĞLU, HURİYE NURSEL (BMJ PUBLISHING GROUP, 2012)
Background Brachyolmia is a heterogeneous group of skeletal dysplasias that primarily affects the spine. Clinical and genetic heterogeneity have been reported; at least three types of brachyolmia are known. TRPV4 mutations have been identified in an autosomal dominant form of brachyolmia; however, disease genes for autosomal recessive (AR) forms remain totally unknown. We conducted a study on a Turkish family with an AR brachyolmia, with the aim of identifying a disease gene for AR brachyolmia. Methods and results We examined three affected individuals of the family using exon capture followed by next generation sequencing and identified its disease gene, PAPSS2 (phosphoadenosine-phosphosulfate synthetase 2). The patients had a homozygous loss of function mutation, c.337_338insG (p.A113GfsX18). We further examined three patients with similar brachyolmia phenotypes (two Japanese and a Korean) and also identified loss of function mutations in PAPSS2; one patient was homozygous for IVS3+2delT, and the other two were compound heterozygotes for c.616-634del19 (p.V206SfsX9) and c.1309-1310delAG (p.R437GfsX19), and c.480_481insCGTA (p.K161RfsX6) and c.661delA (p.I221SfsX40), respectively. The six patients had short-trunk short stature that became conspicuous during childhood with normal intelligence and facies. Their radiographic features included rectangular vertebral bodies with irregular endplates and narrow intervertebral discs, precocious calcification of rib cartilages, short femoral neck, and mildly shortened metacarpals. Spinal changes were very similar among the six patients; however, epiphyseal and metaphyseal changes of the tubular bones were variable. Conclusions We identified PAPSS2 as the disease gene for an AR brachyolmia. PAPSS2 mutations have produced a skeletal dysplasia family, with a gradation of phenotypes ranging from brachyolmia to spondyloepi-metaphyseal dysplasia.
Keywords: SPONDYLOEPIMETAPHYSEAL DYSPLASIA; SPONDYLOEPIPHYSEAL DYSPLASIA